Membrane transport : a practical approach - Baldwin, Stephen A. (Practical approach series, 2000)
Membrane Transport contains a collection of experimental protocols for the study of proteins responsible for the transport of small molecules across biological membranes. It includes information on the latest methods for production of transport proteins by recombinant DNA technology, and for their investigation by techniques accessible to any well-found laboratory.